Cultivar‐specific plant odour preferences of a generalist aphid parasitoid Aphidius colemani and a possible mechanism for maternal priming of resistance to toxic plant chemistry. (20th November 2018) - van Emden, Helmut F.; Vamvatsikos, Panagiotis; Hardie, Jim
Abstract: Aphidius colemani Viereck, emerging from Myzus persicae (Sulzer) mummies on the Brussels sprout cultivar 'Bedford Winter Harvest' (BWH), responds positively in the olfactometer to the odour of that cultivar in comparison with air. Responses to the odours of other sprout cultivars, cabbage and broad bean could be explained by the humidity from plant leaves. In a choice between BWH and other sprout cultivars, the BWH odour is preferred, or that of cv. 'Red Delicious' (RD) if the parasitoids are reared on RD. This confirms previous work showing that the secondary chemistry of a cultivar is learnt from the mummy cuticle during emergence. Adults emerging from pupae excised from the mummy show a similar but less pronounced preference. Parasitoids developing in aphids on an artificial diet do not discriminate between the odours of BWH and RD, unless allowed contact with a mummy from the same cultivar that the mother develops on. This suggests a cultivar‐specific maternal cue. This cue is speculated to consist of a small amount of the secondary chemistry (probably glucosinolates in the present study) that are left in or on the egg at oviposition, which subsequently induces enzymes that detoxify plant‐derived toxins in the aphid host. Indeed, when parasitoids emerging from diet‐reared aphids are released on aphid‐infested sprout plants, fewer mummies are produced than by parasitoids emerging from mummies of plant‐reared aphids or from excised pupae. Only parasitoids that emerge from mummies of plant‐reared aphids prefer the cultivar of origin as shown by the number of mummified hosts. Abstract : The cultivar specificity of the spectrum of plant volatiles (isothiocyanates) from Brussels sprouts is investigated. The results show maternal priming of parasitoid offspring at oviposition with the glucosinolate spectrum of the maternal host plant. It is speculated that this priming confers resistance to plant toxins in the host aphid.